The strategic planning of SMEs in Malaysia: Types of strategies in the aftermath of economic downturn - Cheng, Wei Hin; Abdul Kadir, Kadzrina; Bohari, Abdul Manaf (2012)
During economic downturns, strategic management might be useful for SMEs as they need strategies to survive. The research here looks at whether formal strategic planning is relevant to SMEs and if the Wheelen and Hunger (2008) strategic planning model is applicable to SMEs in the Asian context.For this paper, the aim is to determine the types of strategies that SMEs used in their planning in the period after the economic downturn in 2008-2009.The sample comprised of SMEs in the northern region of Malaysia which covers Perlis, Kedah and Penang and data was collected between September 2010 and December 2010.The findings show that most of the SMEs have strategic planning which resembles the Wheelen and Hunger strategic planning model suggesting that the model is applicable to SMEs in Malaysia.In addition, SMEs seems to prefer proactive strategies such as corporate growth strategies and differentiation for their business strategies.